Zom-B gladiator - Shan, Darren (Shan, Darren. Zom-B (Series), 2014)
B Smith has decided to live and to fight for good as long as possible, but London is swarming with human mercenaries whose sense of right or wrong dissolved when society did and when they capture B, escape will not be easy.